An overview of industrial minerals in Manitoba - W. R. Gunter (Canadian Institute of Mining, Metallurgy and Petroleum, 1989)
"INTRODUCTIONThis article documents the current non-metallic mineral s resources of Manitoba (Fig. I), and makes comparisons with currently producing deposits in North America and elsewhere in the world. Industrial minerals may lack the glamour of gold, silver or the base metals, but they contributed approximately 20070 to the value of Manitoba's raw materials, and even out-performed our petroleum industry, except during the oil boom of the early eighties (Fig. 2). Values per tonne of industrial commodities can be as high or higher than for base metal ores. Commodity prices (Canadian), listed in the February 1988 issue of Industrial Minerals magazine, are: talc $202.00 - $306.00, sillimanite $427.00; kaolin $69.00 - $270.00; garnet $175.00 - $250.00; and mica $405.00 - $540.00. The prices are converted to Canadian dollars using the prevailing exchange rates of February I, 1988. Some commodities are not sold by weight. Building stone, for example, is sold by the cubic foot. An average rough granite block, 4 ft by 4 ft by 8 ft, is worth approximately $2000 sitting on the quarry 1100r in southeastern Manitoba (Fig. 3).Thus, not all rocks that do not contain sulphides are worthless. Some may be extracted more profitably than either the base or precious-metal bearing varieties.Industrial Mineral CommoditiesThe commodities available in Manitoba are described in two categories: (1) those already in production that have additional development or expansion potential, and (2) those not in production logical information available at this time.Current Industrial Mineral ProductionThe commodities described herein are currently in commercial production in Manitoba (Fig. 4). These mineral products also have good market expansion potential provided additional geological and market research is conducted. The use of company names in reference to sundry products and locations should not be interpreted as specific endorsement by the Government of Manitoba. The numbers following the commodity name refer to Figure 1. that have good development potential on the basis of geo-"